To Be a Minority Teacher in a Foreign Culture Empirical Evidence from an International Perspective - Gutman, Mary; Jayusi, Wurud; Beck, Michael; Bekerman, Zvi (Springer International Publishing : Imprint: Springer, 2023)
This open access book offers in depth knowledge on the challenges and opportunities offered by the inclusion of minority teachers in mainstream educational settings from an international perspective. It aims to be a unique and important contribution for scholars, policy-makers, and practitioners considering the complexities brought about by global trends into national/local educational systems and settings. It will also serve to guide future research, policy, and practice in this important field of inquiry. The work will contribute answers to questions such as: How do immigrant/minority teachers experience their work in mainstream educational settings?; How do mainstream shareholders experience the inclusion of immigrant/minority teachers in mainstream educational settings?; What is the effect of the successful (and/or unsuccessful) integration of minority teachers and teacher educators into mainstream education settings?.